Sex Effects on Smoking Cue Perception in Non-Smokers, Smokers, and Ex-Smokers: A Pilot Study - Zanchi, Davide; Brody, Arthur; Borgwardt, Stefan; Haller, Sven (Frontiers in Psychiatry, 2016)
Introduction Recent neuroimaging research suggests sex-related brain differences in smoking addiction. In the present pilot study, we assessed gender-related differences in brain activation in response to cigarette-related video cues, investigating non-smokers, smokers and ex-smokers. Methods First, we compared 29 females (28.6±5.3) versus 23 males (31.5±6.4) regardless of current smoking status to assess global gender-related effects. Second, we performed a post-hoc analysis of non-smokers (9 F, 8M), smokers (10F, 8M) and ex-smokers (10F, 7M). Participants performed a block-design functional magnetic resonance imaging (fMRI) paradigm contrasting smoking with control cue video exposures. Data analyses included task-related general linear model, voxel-based morphometry (VBM) of gray matter, and tract-based spatial statistics (TBSS) of white matter. Results First, the global effect regardless of current smoking status revealed higher activation in the bilateral superior frontal gyrus and anterior cingulate cortex for females compared to males. Second, the analysis according to current smoking status demonstrated higher activation in female vs. male smokers vs. non-smokers in the superior frontal gyrus, anterior and posterior cingulate cortex, and precuneus, and higher activation in female vs. male ex-smokers vs. non-smokers in the right precentral gyrus, in the right insula and anterior cingulate cortex. No structural differences were found in grey or white matter. Conclusion The current study identifies gender-related brain functional differences in smokers and ex-smokers compared to non-smokers. The current work can be considered as a starting point for future investigations into gender differences in brain responses to cigarette-related cues.